Lung functions in children with Type 1 diabetes mellitus: A cross sectional study - Somashekhar, A R; Nagarajan, S A; -, Saketh; Mallikarjuna, H B; Kumar, B M Sunil (Indian Journal of Child Health, 2014)
Background: Diabetes mellitus (DM) is a metabolic disorder precipitating micro and macro vascular complications and peripheral vascular diseases. Normal lung mechanism and gas exchange are influenced by integrity of pulmonary connective tissues and microvasculature. Abnormality in either of these two structural components of lung leads to variations in lung functions. Objective: This study was conducted to document lung function patterns by spirometry in patients with Type 1 DM. Materials and Methods: This cross-sectional study was conducted in Bangalore, India. Patients in the age group of 1-18 years diagnosed with Type 1 DM between December 2009, and January 2011 were included. Data regarding respiratory symptoms, age, height and weight of each patient with Type 1 DM was collected. The children were trained to use spirometers. Multiple readings of forced expiratory volume in one second and forced vital capacity were obtained until consistent, and the best reading was recorded and analyzed for any association. Results: A total of 51 children with Type 1 DM were studied, of whom 24 children were males, with a mean age of 14.06 ± 3.25 years, the minimum age being 5 years and a maximum being 18 years. 25 children (49%) with Type 1 DM were found to have pulmonary dysfunction, of which 19 children (76%) had restrictive lung pattern, and six children (24%) had obstructive pattern. Conclusion: Spirometry evaluation showed that restrictive lung pattern was very common in children with Type 1 DM, and there is scope for further study.